Superconductor-based quaternary photonic crystals for high sensitivity temperature sensing - Soltani, Osswa; Francoeur, Sebastien; Kanzari, Mounir (Chinese journal of physics (Taipei), 2022)
•The transmission properties in 1D superconductor-dielectric quaternary photonic crystal are studied.•The band gap and the defect mode shift to higher wavelengths with increasing the temperature at an average rate of over the range from 10 to 80K.•The temperature sensitivity can be enhanced to a value of with high quality factor up to by simply scaling the structure thicknesses by.•The influences which come from incident angle for both polarizations are analyzed. We have numerically studied the transmission spectra of dielectric-superconductor photonic crystals for temperature sensing and tunable filtering applications in the visible and near-infrared spectral ranges. The 1D structure studied is a multilayer system composed of two dielectrics, TiO2 (H1 and H2) and SiO2 (L), and a superconductor, YBa2Cu3O7 (S), arranged in two repeated mirrored quaternary sequences: (H1SH2L)5 (LH2SH1)5. The optical spectra show that both the band gap and the defect mode shift to higher wavelengths with increasing the temperature at an average rate of 0.285nm/K over the range from 10 to 80K. This temperature sensitivity can be enhanced to a value of 0.83nm/K by simply scaling the structure thicknesses by 60%. Over a range from 60 to 80K, it can be as high as2.12nm/K. This structure can be used for temperature sensing in the visible and near infrared ranges, from 450nm to 980nm, with high quality factor up to 5×104 , thereby providing high resolution sensing for cryogenic processing and space applications.